(untitled) (Research, Society and Development, 2020)
Introduction: Filaggrin is a structural protein of the skin, essential for the maintenance of the epidermal barrier. Currently, several studies indicate that mutations in the FLG gene, that encodes filaggrin, confer a risk of atopic dermatitis, rhinitis, peanut allergy and asthma. Objective: Analyze existing information on how mutations in the FLG gene influence the development of atopic gait and the benefit of early treatment to prevent its progression. Metodology: Through an integrative literature review, a search was performed in the Bireme and Scielo database using the words: atopic dermatitis, asthma, rhinitis, food hypersensitivity. Only free studies were chosen that met the inclusion criteria. Results and discussion: Nineteen scientific articles were selected. These addressed subjects that were separated and organized by category where the knowledge published through them about the proposed theme was consolidated, syntactically linking them in order to obtain a set of propositions and conclusions from the authors. By analyzing the studies, it was possible to confirm that there is a great correlation between mutations of the FLG gene and the development of several pathologies, with atopic dermatitis being the first to manifest, with a propensity for the appearance of other atopies and food hypersensitivity. Thus, therapeutic of active eczema in childhood can be a primary prevention target for the progression of atopic gait, decreasing the chances of the patient progressing to asthma, rhinitis or peanut allergy.